Performance Evaluation of Strengthening Recycled Coarse Aggregate in Cement Stabilized Mixture Base Layer of Pavement - Junhui Zhang; Cheng Li; Le Ding; Henggang Zhao (Advances in Civil Engineering)
This paper attempts to study the effect of different strengthening methods on recycled coarse aggregate (RCA) reprocessed from construction and demolition (C&D) waste. And it aims to obtain the optimal RCA content in cement stabilized recycled mixture (CSRM) applied in the base layer of pavement. Firstly, three strengthening methods were used to strengthen the RCA. It was revealed that the sodium silicate solution is the best method in a strengthening concentration of 8% and strengthening for five hours. Then, the mechanical experiments under two cement dosages, including unconfined compressive strength, splitting strength, and compressive rebound modulus tests, were carried out. In each cement dosage, five different RCA contents (0%, 25%, 50%, 75%, and 100%) were considered. It was found that, at 5% of cement dosage, the strength of CSRM satisfied the requirements of the base layer of the expressway under heavy traffic load. In the case of 4% of cement dosage, the strength of CSRM which was beyond 50% of RCA content was failed to meet specification requirements. For the failed cases, by strengthening RCA in the best method obtained before, 7 d unconfined strength and crushing value of the CSRM with 50% RCA content could meet the requirements of the subbase of expressways and first-class highways in China; the 75% of the mixture meets the requirements of the second-class highways and below.